26=(2x-6)(x-3)

Simple and best practice solution for 26=(2x-6)(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26=(2x-6)(x-3) equation:



26=(2x-6)(x-3)
We move all terms to the left:
26-((2x-6)(x-3))=0
We multiply parentheses ..
-((+2x^2-6x-6x+18))+26=0
We calculate terms in parentheses: -((+2x^2-6x-6x+18)), so:
(+2x^2-6x-6x+18)
We get rid of parentheses
2x^2-6x-6x+18
We add all the numbers together, and all the variables
2x^2-12x+18
Back to the equation:
-(2x^2-12x+18)
We get rid of parentheses
-2x^2+12x-18+26=0
We add all the numbers together, and all the variables
-2x^2+12x+8=0
a = -2; b = 12; c = +8;
Δ = b2-4ac
Δ = 122-4·(-2)·8
Δ = 208
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{208}=\sqrt{16*13}=\sqrt{16}*\sqrt{13}=4\sqrt{13}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-4\sqrt{13}}{2*-2}=\frac{-12-4\sqrt{13}}{-4} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+4\sqrt{13}}{2*-2}=\frac{-12+4\sqrt{13}}{-4} $

See similar equations:

| 1=m+2-2 | | 2(1/2-c)=12/5 | | 5x(6)=x+14+8x+9+x+17 | | 8x+5=5x+14=13 | | 3x+65=6x+15 | | x+89=85 | | X+24=8+7x | | 8x+5=5+14=13 | | 4(3x-5)=2(6x-10) | | X+15+3x-6+31=180 | | -2-21+4x=3-2(13-2x) | | 4a−6=9+a | | 23x+6=24x+1 | | 3x=x=6 | | 5(x-3)+2x+7=5x+6 | | 72.46+-88.1=x | | k+11=−3k−25+2k | | 8x+5x=5x+14=13 | | 6/16x+2(5+4)=-2+3/8x+20 | | 5(X-3)+7=5x+6 | | 5x=10x+34 | | 2(k-7)=5k | | 4p+1=-5 | | 10k+18=8k+4 | | r+31/2=42/3 | | -1/4x+6=2/3x-28 | | 86+x/3=90 | | 1-1k=6-2k | | X+870=7x | | 10x+10=15x-5=180 | | S=r0 | | (-3x+5)+2(x-3)=-8 |

Equations solver categories